A novel approach to the study of the development of the Chalk's smectite assemblage. (April 2014) - Hu, X. F.; Long, D.; Jeans, C. V.
Abstract: Detrital, volcanic and diagenetic origins have been used to explain the smectite clay assemblage that characterizes the Upper Cretaceous Chalk of Europe. To further the understanding of how clays of different origins may have converged to this characteristic clay mineral assemblage a new approach is put forward for their investigation. This is based upon (1) the correlation that exists between the trace element and stable isotope geochemistry of the calcite cements preserved within Chalk brachiopods and the various diagenetic phases of early lithification and cementation recognized in the Chalk, and (2) an understanding of the process of late diagenetic cementation that has caused regional differences in the hardness of the Chalk. It is suggested that each phase of lithification and associated calcite cementation may preserve the different clay assemblages at various stages in their convergence to the characteristic Chalk smectite assemblage.